Kojic Acid. Issue 5 (September 2016) - Gust, Peter J.; Luke, Janiene D.
Abstract : ABSTRACT: A drug is defined in physiology as being a substance that exerts an effect on the body once it has been ingested. Drugs take many forms in their attempt to enter the body including capsules, injections, creams, ointments, inhalants, liquids, and dermal patches. The purpose of this column is to take a closer look at drugs that are used in the field of dermatology. More specifically, this column hopes to bring an understanding to the reader regarding mechanism of action, administration, dosage, adverse effects, and viable alternatives to each particular drug being discussed. In this article, the role of the drug kojic acid, as a dermatologic treatment for hyperpigmentation disorders, as well as other novel uses will be discussed.